Immobilized lipase on porous ceramic monoliths for the production of sugar-derived oil gelling agent1. Issue 84 (16th September 2015) - Gao, Jing; Feng, Kai; Li, Hongwu; Jiang, Yanjun; Zhou, Liya
<x xml:space="preserve">Abstract</x> Lipase from Candida sp. 99-125 was immobilized on porous ceramic monoliths for the production of sugar-derived oil gelling agent.